Diversity and divergence: the dynamic burden of poor maternal health. Issue 10056 (29th October 2016) - Graham, Wendy; Woodd, Susannah; Byass, Peter; Filippi, Veronique; Gon, Giorgia; Virgo, Sandra; Chou, Doris; Hounton, Sennen; Lozano, Rafael; Pattinson, Robert; Singh, Susheela
Summary: Maternal health is a big issue and is central to sustainable development. Each year, about 210 million women become pregnant and about 140 million newborn babies are delivered—the sheer scale of maternal health alone makes maternal well being and survival vital concerns. In this Series paper, we adopt primarily a numerical lens to illuminate patterns and trends in outcomes, but recognise that understanding of poor maternal health also warrants other perspectives, such as human rights. Our use of the best available evidence highlights the dynamic burden of maternal health problems. Increased diversity in the magnitude and causes of maternal mortality and morbidity between and within populations presents a major challenge to policies and programmes aiming to match varying needs with diverse types of care across different settings. This diversity, in turn, contributes to a widening gap or differences in levels of maternal mortality, seen most acutely in vulnerable populations, predominantly in sub-Saharan Africa. Strong political and technical commitment to improve equity-sensitive information systems is required to monitor the gap in maternal mortality, and robust research is needed to elucidate major interactions between the broad range of health problems. Diversity and divergence are defining characteristics of poor maternal health in the 21st century. Progress on this issue will be an ultimate judge of sustainable development.